The Formation of Abhekteh (Devotional) Character In Children In Family Care of Kyai Madura - Aziz, Thorik; Ardhana Reswari; Ria Astuti; Fadilah; Denok Dwi Anggraini; Rasidi; Devi Kurnia Rahmawati (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to examine the formation of the character "Abhekteh" (devotion) for children in the care of Kyai families in Madura. The concept of "Abhekteh" is a cultural and religious value that underlies the behavior of devotion to parents and elders, which is highly respected in Madurese society. The research method used is a qualitative phenomenological approach to explore the formation of the character of abhekteh (devotion) in children in the care of the families of Madurese kyai with data collection techniques in the form of observation, in-depth interviews, and documentation. The research respondents consisted of kyai families, consisting of fathers (kyai) and mothers (nyai). Data analysis was carried out thematically to understand the mechanism of internalization of Abhekteh values ​​in everyday life. The results of the study indicate that parenting practices in Madurese kyai families to form abhekteh (devotion) characters in children is a complex and multidimensional process. The approach used tends to be authoritative, combining firmness in instilling abhekteh values ​​with warmth and open communication. The main methods used include role models, habituation, dialogue, reflection, and involvement in social activities. The implications of these parenting practices include the internalization of deep moral values ​​in children, the development of emotional and spiritual intelligence, the formation of a strong cultural identity, increased ability to adapt to changing times, the development of social and leadership skills, and the strengthening of family ties and social cohesion of the community.